Covering-Location Models for Emergency Situations That Require Multiple Response Units - Batta, Rajan; Mannur, Narasimha R. (Management Science, 1990)
In this paper we propose a new criterion for coverage which is suitable for two kinds of applications: (i) location of fire trucks in a geographical area in which some demands require multiple fire trucks to be within an acceptable distance standard to achieve coverage; and (ii) location of ambulances in an environment in which a large demand volume often leads to the unavailability of the most desirable response unit. The set covering location problem and the maximal covering location problem are examined in the proposed modeling framework. Properties for these models are developed, and limited computational experience is reported.